Meditation in Qualitative Research for Bracketing and Beyond - Katalin Grajzel (International Journal of Qualitative Methods)
In this study, I recounted my experience using mantra meditation during a phenomenological study for the purposes of bracketing. The efficacy and purpose of bracketing have been debated from Husserl (1931), whose aimed was to achieve objectivity, to Heidegger (1962) who advocated for immersion of the researcher, through the French school (Merleau-Ponty, 1964) of middle ground, by whom bracketing was seen as the process to unearth and suspend biases for the better understanding of participants’ experiences (Arsel, 2017; Creswell & Creswell, 2017; Creswell & Poth, 2016; Fischer & Guzel, 2023). In this study, however, I propose another approach to bracketing that expands beyond phenomenology and the duality of objectivity or immersion. I propose that bracketing, with the aim of meditation is inseparable from qualitative research. Meditation, as a form of bracketing, provokes the researcher to be fully present ensuring that participants’ experiences are heard and interpreted in a faithful manner. In this orientation, the goal of bracketing is not to rid one’s subjectivity but to allow subjectivity to be diminished and the researcher to be fully present to the other.